2018
DOI: 10.3389/fimmu.2018.01640
|View full text |Cite
|
Sign up to set email alerts
|

Evolution of Two Major Zika Virus Lineages: Implications for Pathology, Immune Response, and Vaccine Development

Abstract: Zika virus (ZIKV) became a public health emergency of global concern in 2015 due to its rapid expansion from French Polynesia to Brazil, spreading quickly throughout the Americas. Its unexpected correlation to neurological impairments and defects, now known as congenital Zika syndrome, brought on an urgency to characterize the pathology and develop safe, effective vaccines. ZIKV genetic analyses have identified two major lineages, Asian and African, which have undergone substantial changes during the past 50 y… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

2
107
0
2

Year Published

2019
2019
2023
2023

Publication Types

Select...
7
2

Relationship

0
9

Authors

Journals

citations
Cited by 95 publications
(111 citation statements)
references
References 159 publications
2
107
0
2
Order By: Relevance
“…Available studies suggested that African lineage strains were more virulent. They tended to infect more cells and produce more virus particles, inducing more cell death than the Asian-lineage strains (49,50). The ZIKV MR766 strain isolated from rhesus monkeys from Uganda in 1947 is a classic African-lineage strain, whereas SZ-WIV01 used in our study is isolated from the serum of a 38-yr-old Chinese male patient who had traveled to Fiji and Samoa on February 19, 2016 (6).…”
Section: Discussionmentioning
confidence: 99%
“…Available studies suggested that African lineage strains were more virulent. They tended to infect more cells and produce more virus particles, inducing more cell death than the Asian-lineage strains (49,50). The ZIKV MR766 strain isolated from rhesus monkeys from Uganda in 1947 is a classic African-lineage strain, whereas SZ-WIV01 used in our study is isolated from the serum of a 38-yr-old Chinese male patient who had traveled to Fiji and Samoa on February 19, 2016 (6).…”
Section: Discussionmentioning
confidence: 99%
“…[33][34][35] Genetic analyses indicate that its geographic circulation was limited to the areas around Africa and Asia by the 2000s; ZIKV then evolved into 2 distinct lineages with differential pathogenesisdAfrican (ie, African I lineage) and Asian. [36][37][38] A study published in July 2018 by Beaver et al 39 revealed that the African lineages were more virulent than the Asian and induced stronger inflammatory responses. However, it is not clear why neurologic disorders and congenital malformations throughout the Americas are mainly associated with the Asian lineage strains.…”
Section: Zika Virusmentioning
confidence: 99%
“…40 The Asian strains have been found to activate innate immune interferon (IFN) regulatory factors via NS1, NS4B, and NS5 ZIKV nonstructural proteins while African lineage strains have not, demonstrating evolutionary differences in pathogenesis and molecular responses between Asian and African lineages. 39,41 The Zika genome is analogous to that of other Flaviviridae RNA viruses (ie, yellow fever, Japanese encephalitis, West Nile, tick-borne encephalitis, and dengue type 1-4 viruses) and encodes for 3 major structural proteins (ie, prM, capsid [C], and E [a primary target of neutralizing antibody development]) and 7 nonstructural proteins (ie, NS1, NS2A, NS2B, NS3, NS4A, NS4B, and NS5). Notably, the nonstructural NS5 protein is implicated in RNA synthesis and viral replication.…”
Section: Zika Virusmentioning
confidence: 99%
“…The detection of ZIKV in Asia related to major outbreaks and Guillain Barré Syndrome, and subsequently in the Americas causing congenital microcephaly highlighted the possibility of a sylvatic cycle establishment 5 . African lineages of ZIKV have never been detected in the Americas, these lineages of ZIKV were only isolated from mosquito pools and NHP samples, while naturally occurring ZIKV from Asian lineage was mostly isolated from human samples and mosquitoes 6 . However, the circulation of epidemic strain of ZIKV in capuchin monkeys (Sapajus apella) and marmosets (Callithrix penicillata) was evidenced in Brazil 2,7,8 .…”
Section: Introductionmentioning
confidence: 99%